Analysis of Factors Related to Nutritional Status of Toddlers Aged 12-59 Months - Rizkiyah Novianti; Rinang Mariko; Yantri Maputra (GLOBAL HEALTH SCIENCE GROUP, 2026)
The nutritional status of toddlers is influenced by factors such as immunization history, exclusive breastfeeding history, maternal knowledge, socioeconomic status, and parenting patterns. This study aims to identify risk factors associated with the nutritional status of toddlers aged 12-59 months in the working area of the Padang Pasir Community Health Center. This is an observational analytical study with a cross-sectional design. This study aims to determine the relationship between the history of exclusive breastfeeding, maternal knowledge, socioeconomic status, and parenting patterns with nutritional status in toddlers in the Padang Pasir Community Health Center work area. The sample consisted of 351 mothers with toddlers aged 12-59 months, selected using proportional sampling. Data collection used a questionnaire. Data were analyzed using chi-square analysis, logistic regression multinomial. The results of the quantitative research using chi-square test showed a relationship between exclusive breastfeeding (p=0.032), maternal knowledge (p=0.010), parental income (p=0.003), feeding parenting patterns (p=0.008) with the nutritional status of toddlers aged 12-59 months. The most dominant factor was feeding parenting patterns (OR=1.302). The study concluded that parenting and feeding patterns were the most closely related factor to the nutritional status of toddlers aged 12-59 months. Community health centers are expected to improve parenting through routine counseling, information media, and direct information on the importance and negative impacts of inadequate parenting and feeding patterns on children's nutritional status.